2010
DOI: 10.1364/josaa.27.001541
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between radius and asphericity in surfaces fitted by conics

Abstract: The optical surfaces of the eye are often described in terms of their radius and asphericity. The variations caused by experimental noise in repeated measurements of radius and asphericity of the same surface are strongly correlated. We show this correlation in experimental corneal elevation data from videokeratoscopy and Scheimpflug topography, in non-contact profilometry data of artificial lenses, and in simulations. The effect is a characteristic of the fits to conic curves, and not restricted to any experi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…The denoised surfaces were also fitted by quadrics. For the purposes of this study a spherical surface was used as a reference surface in corneal elevation maps, A biconicoid was used to obtain corneal shape descriptive parameters (radii of curvature R x and R y and conic constants Q x and Q y ) [40]. …”
Section: Methodsmentioning
confidence: 99%
“…The denoised surfaces were also fitted by quadrics. For the purposes of this study a spherical surface was used as a reference surface in corneal elevation maps, A biconicoid was used to obtain corneal shape descriptive parameters (radii of curvature R x and R y and conic constants Q x and Q y ) [40]. …”
Section: Methodsmentioning
confidence: 99%
“…Manns et al reported, for the first time, measurements of the lens asphericity ex vivo [21]. Interaction effects between lens radius of curvature and asphericity in the lens profile fittings suggest that those values should not be interpreted separately [23]. Dubbelman et al showed that the asphericity of human lenses in vivo tends to increase with age for both anterior and posterior surface [22].…”
Section: Introductionmentioning
confidence: 99%
“…The gradient index parameters were obtained using a reconstruction method based on optimization of optical path differences, described in detail elsewhere [23], which produced the following values: n c = 1.44319; n s = 1.37351; r pp = −3.52546 mm. Given the potential interactions between radius of curvature and asphericity [24], the differences between the nominal (measured) and simulated surfaces are given in terms of the RMS difference of their elevation. A summary of this simulation is illustrated in the top panel of Fig.…”
Section: Methodsmentioning
confidence: 99%